2022
DOI: 10.1002/aepp.13285
|View full text |Cite
|
Sign up to set email alerts
|

Consumer willingness to pay for environmentally sustainable meat and a plant‐based meat substitute

Abstract: We investigate consumers' willingness to pay premiums for environmentally sustainably produced meat and plant‐based meat substitutes. We conducted a randomized control study coupled with an incentive‐compatible experimental auction. Treatment consisted of information nudges concerning the environmental and health externalities of meat production and consumption. Results show that demand for sustainably produced beef and a plant‐based meat substitute is inelastic. We elicited participants' time preferences to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 59 publications
(73 reference statements)
0
14
0
Order By: Relevance
“…Similarly, Fesenfeld et al (2021) found that despite health framed messages increasing individuals' concern about the impact of meat and fish consumption, these increased levels of concern do not translate into changes in behavioral intentions, willingness to pay, and demand‐side policy support. In line with this result, Katare et al (2022) provided evidence on the ineffectiveness of environmental and health information nudges at motivating consumers to pay price premiums for environmentally sustainably produced meat and plant‐based substitutes.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Similarly, Fesenfeld et al (2021) found that despite health framed messages increasing individuals' concern about the impact of meat and fish consumption, these increased levels of concern do not translate into changes in behavioral intentions, willingness to pay, and demand‐side policy support. In line with this result, Katare et al (2022) provided evidence on the ineffectiveness of environmental and health information nudges at motivating consumers to pay price premiums for environmentally sustainably produced meat and plant‐based substitutes.…”
Section: Resultsmentioning
confidence: 89%
“…Thus, to increase consumers' motivation towards healthy and sustainable diets, nudges emerge as a key trigger to change consumers' behavior while maintaining their freedom of choice (Thaler & Sunstein, 2009). Behavioral interventions aimed to reduce meat consumption, such as the Meatless Monday campaign implemented in New York City public schools (Meatless Monday, 2019), usually provide individuals with information associated with the health and environmental benefits of reducing meat consumption (Campbell‐Arvai et al, 2014; Cordts et al, 2014; Graham & Abrahamse, 2017; Katare et al, 2022; Wolstenholme et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of the PBM industry to price its products competitively with respect to conventional meat is one of the keys to success. The higher consumer acceptability of PBM depends on price equality with animal meat, which is related to the capability of the industry to scale up production [ 31 , 101 ]. PBM needs to become more affordable to compete with animal-based meat products, as affordability is associated with purchasing intentions.…”
Section: Economic Sustainabilitymentioning
confidence: 99%
“…Nos résultats identifient également deux types INTRODUCTION Food safety problems together with environmental pollution, part of which may result from agricultural production, have caused serious health damages and emerged as a significant concern in the world (Pouliot & Wang, 2018;WHO, 2015), especially in developing countries, including China (Midingoyi et al, 2019;Wu et al, 2016;Zhang et al, 2017). The demand for safe and eco-friendly food has been growing, and consumers are willing to pay a price premium for various labels and claims for these food attributes, such as organic, sustainable, and green-food (Gerini et al, 2016;Jiang et al, 2019;Katare et al, 2022). Meanwhile, as the food system becomes rapidly industrialized, large scale farming gains advantages in producing standardized conventional food at a lower cost.…”
mentioning
confidence: 99%